PENGARUH KEJELASAN SASARAN ANGGARAN DAN SENJANGAN ANGGARAN TERHADAP KINERJA PEJABAT ESELON III DAN IV PADA DINAS KESEHATAN KOTA KENDARI - Abdullah, Muntu; Aswati, Wa Ode; Astrinigita, Astrinigita (JURNAL AKUNTANSI DAN KEUANGAN, 2017)
Â ABSTRACTÂ The purpose of the reseearch is knowing The Effect of Budget Target Clarity and Budgetary Slack to Performance Echelon III and IV on Kendari City Health Department, which can be viewed either parsial and simultan. The methods of data analysis used in this research is descriptive analysis method and multiple linear regression analysis method. The method of data collection use is the method of questionnaires that as many as 15 people Echelon III dan IV on Kendari City Health Department. The results of this study showed that partially Budget Target Clarity significant effect to Performance Echelon III and IV and Budgetary Slack no significant effect to Performance Echelon III and IV. Simultaneously, Budget Target Clarity and Budgetary Slack significant effect to Performance Echelon III and IV. This study also shows the coefficient of determination for Budget Target Clarity and Budgetary Slack significant effect on Performance Echelon III and IV of R2 = 0.799. The figure has meaning that the contribution of the variables X1 and X2 to Y is 79.9% and the remaining 20.1% is influenced by other factors.Keywords: Budget Target Clarity, Budgetary Slack, Performance Echelon III and IV